2021
DOI: 10.3390/ijms22115905
|View full text |Cite
|
Sign up to set email alerts
|

Presence of β-Lactamase-producing Enterobacterales and Salmonella Isolates in Marine Mammals

Abstract: Marine mammals have been described as sentinels of the health of marine ecosystems. Therefore, the aim of this study was to investigate (i) the presence of extended-spectrum β-lactamase (ESBL)- and AmpC-producing Enterobacterales, which comprise several bacterial families important to the healthcare sector, as well as (ii) the presence of Salmonella in these coastal animals. The antimicrobial resistance pheno- and genotypes, as well as biocide susceptibility of Enterobacterales isolated from stranded marine ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 136 publications
(169 reference statements)
2
22
0
Order By: Relevance
“…The chlorhexidine MICs determined in the present study were in a similar range, although we could not detect E. coli isolates with the lowest and highest MICs of 0.00003% and 0.002%. In a third study, 27 E. coli isolates from marine mammals exhibited benzalkonium chloride MICs that ranged between 0.000125 and 0.002%, with most isolates (24/27) displaying a MIC of 0.002% [ 59 ]. The corresponding chlorhexidine MICs were distributed over six dilution steps from 0.0003% to 0.001% with the majority of isolates (24/27) ranging between 0.00006 and 0.0005% [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chlorhexidine MICs determined in the present study were in a similar range, although we could not detect E. coli isolates with the lowest and highest MICs of 0.00003% and 0.002%. In a third study, 27 E. coli isolates from marine mammals exhibited benzalkonium chloride MICs that ranged between 0.000125 and 0.002%, with most isolates (24/27) displaying a MIC of 0.002% [ 59 ]. The corresponding chlorhexidine MICs were distributed over six dilution steps from 0.0003% to 0.001% with the majority of isolates (24/27) ranging between 0.00006 and 0.0005% [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, 27 E. coli isolates from marine mammals exhibited benzalkonium chloride MICs that ranged between 0.000125 and 0.002%, with most isolates (24/27) displaying a MIC of 0.002% [ 59 ]. The corresponding chlorhexidine MICs were distributed over six dilution steps from 0.0003% to 0.001% with the majority of isolates (24/27) ranging between 0.00006 and 0.0005% [ 59 ]. Again, these MICs were in an excellent agreement with the benzalkonium chloride and chlorhexidine MICs determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of resistant E. coli was higher in the samples from the Baltic Sea (44.4%) compared to those from the North Sea (33.3%), but without statistical significance. Although not many studies have investigated antimicrobial resistance in marine mammals thus far, resistant bacteria have been reported in various marine mammal species, including pinnipeds and cetaceans from different areas of the world [ 8 , 83 , 84 , 85 , 86 , 87 ]. The occurrence of resistant E. coli isolates varied in the different studies, with reported figures of 10% [ 86 ], 26.9% [ 87 ], 47% [ 8 ], and 50% [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance, defined as resistance to at least one antimicrobial of three or more antimicrobial classes [ 89 ], occurred in the present study in 37.2% of the resistant E. coli isolates, which is in accordance with an Irish study on harbour and grey seals that found multidrug resistance in 43.5% of the E. coli isolates [ 90 ]. Another study investigating Enterobacterales observed a higher prevalence, with 71% of the isolates exhibiting multidrug resistance [ 85 ]. In the present study, harbour porpoises were found to carry significantly higher numbers of multidrug-resistant E. coli isolates compared to the investigated seal species, while there was no significant difference between species regarding the carriage of E. coli isolates with resistance to at least one antimicrobial drug.…”
Section: Discussionmentioning
confidence: 99%
“…Biocides are used to control infectious diseases on poultry farms and in slaughterhouses and can contribute to the emergence and spread of bacteria resistant to antibiotics [ 54 , 55 ]. In addition, resistance to biocides has already been reported.…”
Section: Discussionmentioning
confidence: 99%